KUALITAS PELAYANAN PERUSAHAAN UMUM DAERAH AIR MINUM TIRTO NEGORO KABUPATEN SRAGEN - Joko Pramono; Haryanti Haryanti; Winarti Winarti (Master of Public Administration, Universitas Slamet Riyadi, 2023)
Perusahaan Umum Daerah Air Minum Tirto Negoro is a Regional Owned Enterprise (BUMD) of the Sragen Regency Government which operates provide services for the provision and distribution of drinking water to the community. But at the age of 43 years, Perumda Sragen still has many problems faced in providing services.The purpose of this research is to find out how the service quality of Perumda Sragen. The researcher used a qualitative descriptive approach and purposive sampling technique. Data collection techniques through observation, interview and documentation.The problems that occurred in Perumda Sragen are the number of pipe leaks due to old age causing dirty and cloudy water; damaged water meters; small water discharge during Lebaran Day due to more usage than normal days; and less thorough PPOB (Payment Point Online Banking) payment counter which causes payment errors from customers.The result of this study indicates that the service from Perumda Sragen in terms of the availability of infrastructure and facilities, reliability, and guarantee are good, but only in terms of empathy is being a note to make improvements in providing services to the customers. Keywords: Service, Quality, Perumda Air Minum Tirto Negoro